Frameworks of IT prosumption for business development - Pankowska, Magorzata (Hershey : Business Science Reference, 2014)
"This book investigates the latest empirical research on active use of information technology resources, enabling users with new methodologies, tools, and opportunities to impact application development processes"--Provided by publisher
Theoretical considerations on IT prosumption and prosumers -- Qualitative and quantitative research on IT prosumption development and evaluation -- ICT development for prosumers and produsers -- ICT prosumption applications' review
Includes bibliographical references and index
13
Keywords: Business enterprises -- Technological innovations; Decision support systems